The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/jep.12400
|View full text |Cite
|
Sign up to set email alerts
|

A semi‐quantitative and thematic analysis of medical student attitudes towards MLearning

Abstract: As one of the largest evaluative and only quantitative study of smartphone-assisted M-Learning in undergraduate medical education, MBChB Mobile suggests that smartphone and application technology enhances students' learning experience. Barriers to implementation may be addressed through the provision of tailored learning resources, along with user-defined support systems, and appropriate means of ensuring acceptability to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 21 publications
2
48
0
Order By: Relevance
“…Some practice mentors reportedly reinforced this by deeming it unacceptable (unlike notebook and pen) to use the device in front of clients. Green et al (2015) found that only 29.2% of 274 senior medical students (strongly) agreed with: "I consider it professional to use an iPhone in a clinical setting," despite receiving an official device loaded with academic, assessment, and logging/ reflective software for such use. Consequently, that medical school provided branded cases for the clinical setting, reinforcing that mobile learning represented the official curriculum.…”
Section: Evidence For Context From Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some practice mentors reportedly reinforced this by deeming it unacceptable (unlike notebook and pen) to use the device in front of clients. Green et al (2015) found that only 29.2% of 274 senior medical students (strongly) agreed with: "I consider it professional to use an iPhone in a clinical setting," despite receiving an official device loaded with academic, assessment, and logging/ reflective software for such use. Consequently, that medical school provided branded cases for the clinical setting, reinforcing that mobile learning represented the official curriculum.…”
Section: Evidence For Context From Systematic Reviewsmentioning
confidence: 99%
“…The mobile device facilitated such performance analysis. Besides use in mini-CEX (Ferenchick et al 2013;Green et al 2015), other assessment uses included: Snodgrass et al's (2016) pilot study evaluated favorably formative feedback via iPADs for physiotherapy, occupational therapy, and speech pathology students on clinical placement, using free text and standard statements (mapped to national discipline-specific competencies). The very small study-sample and insufficient detail about analyzing free-text comments weakened this evidence, but overall most students evaluated the system positively, e.g.…”
Section: Evidence For Context From Systematic Reviewsmentioning
confidence: 99%
“…There are some studies that investigate about the trends of mobile learning [10], the perception of students or teachers [11][12][13][14], their challenges [11,15,16], benefits [11,17,18] but there are few of them related with the real impact of mobile learning [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…As the type of hardware might be a major hurdle for the adoption of e-learning resources, many schools have started to either require students to buy and bring their own electronic devices or to make them available as part of the learning environment. 32,33 Although the number of students who reported device challenges in our study was small, it remains an important consideration when designing e-learning resources to accommodate users that are unfamiliar with how to navigate high-tech tools, do not have access to a smartphone or tablet, lack the necessary technological environment, and/or are experiencing website or app dysfunctions. Having e-learning resources available in different interfaces to accommodate a maximal number of students and technological environments may therefore be a good choice.…”
Section: Discussionmentioning
confidence: 96%